(untitled) (Medico Legal Update, 2021)
Dental health problems suffered by many people in Indonesia is dental caries. Poor dental and oral hygiene is one of the factors causing dental caries or oral and dental health problems. Teaching oral health with demonstration method can improve tooth brushing skills and reduce oral and dental hygiene in early childhood. This study aims to the effectiveness of counseling with brushing demonstration method as an effort to improve tooth brushing skills and the status of dental hygiene in early childhood in school. Method: this study used a quasy experiment with a pretest and posttest with one group design. This research was conducted at Kindergarten Dharma Putra Nusantara 86 Cilandak District, South Jakarta City. Independent variable: counseling by demonstration method and the dependent variable: brushing skills and the status of early childhood dental and oral hygiene. Data were tested using Wilcoxon. Results: counseling with a tooth brushing demonstration method was effective in improving brushing skills (p <0.001) and effective in improving the status of early childhood dental and oral hygiene (p <0.001). Conclusion: Counseling with the demonstration method of tooth brushing is effective as an effort to improve tooth brushing skills and the status of dental and oral hygiene in early childhood at school.